Effects of grassland degradation on soil ecological stoichiometry and soil microbial community on the South of the Greater Khingan Mountains - Li, Yuyu; Zhao, Lixing; Hilal, Mian Gul; Guo, Lizhu; Zhang, Yandong; Ji, Yu; Jiang, Xiaowei; Hao, Lifen; Lin, Kejian (Frontiers in Microbiology, 2024)
Grassland which covers 40% of terrestrial land is an important ecosystem having a multitude of functions, which has suffered various degrees of degradation with the interaction between global climate change and unreasonable human utilization (e.g., grazing and reclamation). Improved understanding of soil and microbial community diversity during meadow steppe degradation is crucial for predicting degradation mechanisms and restoration strategies. Here, we used Illumina sequencing technology to investigate the patterns of soil microbial community structure and the driving factors of its change across different degradation degrees of meadow steppe [i.e., non-degraded grasslands (NDG), lightly degraded grasslands (LDG), moderately degraded grasslands (MDG), and severely degraded grasslands (SDG)] south of the Greater Khingan Mountains. Our results showed a significant variation in soil properties, enzyme activity, and soil metal elements across the degraded meadows. Soil available phosphorus (AP), urease (UE), and cellulase (CL) in soils increased with the intensity of grassland degradation. Grassland degradation significantly decreased soil bacterial and fungal richness. In addition, grassland degradation significantly increased the relative abundance of Firmicutes (from 1.65% to 5.38%) and Myxococcota (from 2.13% to 3.13%). Degradation considerably increased the relative abundance of Ascomycota (from 66.54% to 75.05%), but decreased Basidiomycota (from 18.33% to 9.92%). The relative abundance of nitrogen fixation and cellulolysis decreased significantly due to grassland degradation. For fungal functional guilds, the relative abundance of pathotrophs increased while saprotrophs decreased significantly with increasing severity of degradation. Total nitrogen (TP), AP, available potassium (AK), manganese (Mn), lead (Pb), UE, sucrase (SC), and alcalase protease (ALPT) were the main drivers of soil bacterial community composition, while TP, AP, AK, Pb, UE, and SC were the main drivers of soil fungal community composition in the degraded grassland. Our findings demonstrated that severe grassland degradation has an enormous effect on soil microbial communities and soil physicochemical dynamics. These findings improve our theoretical understanding of the interactions between soil microbial populations and soil environmental variables in degraded grassland.